Quality-by-design applied development of tianeptine sodium sustained-release once-a-day dosing tablet - Son, Jae Woon; Kim, Hyung Chul; Kim, Do Hyub; Ahn, Joon Yong; Park, Young Joon; Kim, Joo Eun (Journal of Pharmaceutical Investigation, 2024)
Purpose: Tianeptine sodium, a selective serotonin reuptake enhancer commonly prescribed for the treatment of various mood disorders, has a short half-life (t1/2) and is currently available only as an immediate-release tablet administered three times daily, while the development of sustained-release formulations for tianeptine sodium remains limited. Therefore, this study developed a once daily sustained-release tablet for tianeptine sodium to improve overall patient compliance. Methods: We manufactured sustained-release double-layer tablets by applying a Gastro-Retentive Drug Delivery System (GRDDS) to simultaneously generate an immediate and sustained drug release. In addition, to address the issues associated with optimizing sustained-release drug formulations, the Quality-by-Design (QbD) approach was applied. Results: The final formulation exhibited a dissolution pattern optimized for sustained release that proved stable for 6 months under accelerated conditions, and a dissolution rate of approximately 100% over 24 h. Furthermore, pharmacokinetic analysis revealed that the newly formulated double-layer tablets showed typical characteristics of sustained-release tablets, including appropriate Tmax, longer t1/2, and equivalent systemic exposure of tianeptine sodium compared with that after three times dosing of Stablon® tablets a day. Conclusion: Taken together, these results suggest that administration of a single daily dose of the tianeptine sodium sustained-release (TSR) tablet may prove effective for the treatment of depression, while improving patient compliance. Moreover, this platform can be used to overcome current commercial limitations as it can be applied to manufacture various immediate-release formulations in sustained-release form.
Keywords: Gastro-retentive drug delivery system; Patients’ compliance; Pharmacokinetics study; Quality-by-design approach; Sustained-release double-layer tablets; Taken once a day; Tianeptine sodium